Transparency in Global Environmental Governance - Aarti Gupta, Michael Mason (The MIT Press, 2014)
As this book goes to press in late 2013, Edward Snowden, the US National Security Agency â€œwhistleblower,â€ is suspended in limbo in Russia, unable to make his way out; and the geopolitics of surveillance versus transparency (and its consequences for diplomacy, human rights, national sovereignty, and global security) is front-page news everywhere. Debates rage about whether Snowden is a traitor or a hero for revealing that the United States is engaged in covert surveillance of its own citizenry, the citizenry of other countries, and of (friendly and not so friendly) governments worldwide. In light of these revelations, the need for transparency to disclose what the powerful are doing, and to hold them to account, seems ever more urgent. Yet, even as the practices of surveillance are routinely condemned, its counterpart, transparency, is not necessarily the panacea that it is made out to be. This is so whether transparency is about the practices of surveillance (as with Snowdenâ€™s revelations) or about national security threats, the practices of war and diplomacy, financial and economic relations, or even (relatively more benignly) about the environmental performance of different powerful actors. This book explores the claim that transparency is not a panacea by addressing the workings of transparency and disclosure in the global environmental and sustainability realm. Although transparency has always been front and center in certain domains of international relations, its power and its promise to effect desired changes in global sustainability governance is only now receiving more attention. This edited book extends this line of research much further. It undertakes a wide-ranging (comparative) analysis of diverse areas of global environmental governance, in which transparency and information disclosure play a key role. It deploys, as starting hypotheses, some of the central findings of the GEP special issue and subjects these to further empirical and comparative analysis. It includes fourteen contributions, including three context-setting conceptual treatments of transparency in governance and ten empirical examples of governance by disclosure. Four of these draw on the earlier GEP special issue articles, yet each one has undergone a significant metamorphosis in order to engage with the specific analytical framework advanced in this book. Two of the short GEP commentaries are also included in this book, yet now as full-length research contributions. Supplementing these are eight new chapters written exclusively for this book.